Escherichia coli tRNA 2‐selenouridine synthase (SelU) converts S2U‐RNA to Se2U‐RNA via S‐geranylated‐intermediate. Issue 13 (19th June 2018) - Sierant, Malgorzata; Leszczynska, Grazyna; Sadowska, Klaudia; Komar, Patrycja; Radzikowska‐Cieciura, Ewa; Sochacka, Elzbieta; Nawrot, Barbara
Abstract : To date the only tRNAs containing nucleosides modified with a selenium (5‐carboxymethylaminomethyl‐2‐selenouridine and 5‐methylaminomethyl‐2‐selenouridine) have been found in bacteria. By using tRNA anticodon‐stem‐loop fragments containing S2U, Se2U, or geS2U, we found that in vitro tRNA 2‐selenouridine synthase (SelU) converts S2U‐RNA to Se2U‐RNA in a two‐step process involving S2U‐RNA geranylation (with ppGe) and subsequent selenation of the resulting geS2U‐RNA (with SePO3 3− ). No 'direct' S2U‐RNA→Se2U‐RNA replacement is observed in the presence of SelU/SePO3 3− only (without ppGe). These results suggest that the in vivo S2U→Se2U and S2U→geS2U transformations in tRNA, so far claimed to be the elementary reactions occurring independently in the same domain of the SelU enzyme, should be considered a combination of two consecutive events – geranylation (S2U→geS2U) and selenation (geS2U→Se2U). Abstract :